БОШЛАНҒИЧ ТАЪЛИМДА ЎҚУВЧИЛАРНИНГ ЎҚИБ ТУШУНИШ МАЛАКАСИНИ ШАКЛЛАНТИРИШНИНГ ДИДАКТИК ТАЪМИНОТИ - Абдижамилова, М.М. (SCIENCE and SOCIETY, 2023)
This article describes the process of acquiring artistic experience in the formation of reading skills and understanding of works of art, as well as the process of assimilation and interpretation by reading informational works in primary school students.
Keywords: skill and experience; text reading; reading comprehension; association